Sufi Turuq and the politics of democratization in Senegal*. Issue 2 (3rd May 2016) - Diallo, El Hadji Samba; Kelly, Catherine Lena
Abstract: The Senegalese example is often used to suggest that Muslim-majority countries are capable of democratizing if the state is equidistant from all religions. Historically, Islam lacks a hegemonic status in Senegal's legal order, and national politics exhibits the "twin tolerations, " the mutually respectful relationships between religious and governmental authorities that are necessary for democracy. These continuities cannot explain why Sufi orders ( turuq ) changed from supporting a single-party authoritarian system in the 1960s–1980s to reinforcing serious electoral contestation as of the 1990s; economic crisis fostered the change. During structural adjustment in the 1980s, economic shocks weakened the ruling party, inducing it to negotiate a democratic electoral code with opponents. The reforms significantly increased electoral uncertainty by the late 1990s, which changed the behavior of state and religious actors. Abdoulaye Wade broke the tradition of presidential neutrality towards religion, favoring Murids over Tijāns in hope of getting re-elected by Murid voters. Turuq members more frequently created political parties (to oppose or collaborate with the president) or grassroots movements (to denounce government corruption and anti-democratic practices). The history of the "Senegalese social contract" suggests why movements more successfully channeled democratic energies, while parties led by Sufi figures had limited impact.